The Application of Rational-Emotive Behavior Therapy to Reduce Stress among Mother with Leukemia Children - Yuni Sufyanti Arief; Ilya Krisnana (Jurnal Ners, 2014)
Introduction: A child who is diagnosed with Leukemia will undergo several procedures are long and painful action. During the process of hospitalization due to leukemia children and parents can experience a variety of events or actions handling according to various studies shown by the experience very traumatic and stressful (Supartini 2004 in Arif, SY, 2007). Some of the methods used to deal with anxiety is psikoprofilaksis, relaxation and imagination (Reeder et al., 2011). Rational-emotive behavior therapy by Albert Ellis in 1990 describes a unique man who is basically have a tendency to think rational and irrational.Methods: aim of this study is to explain the effect of Rational Emotive Behavior Therapy (REBT) for stress levels of mothers with children suffering from Leukemia. The study design used was a pre-experiment Quasy-post control group design. The sample was 10 mothers of children diagnosed with leukemia are treated in a child hematology ward Soetomo hospital. Variable in this study is the level of depression and anxiety mothers with children suffering from leukemia.Result: Based on the results obtained Wilcoxon statistical test p = 0.025 in the treatment group and p = 0.32 in the control group. Mann Whitney test results obtained p = 0.012.Conclution: Rational-emotive behavior therapy can reduce levels of depression and anxiety (stress) mothers with children suffering from leukemia. It is expected that the application of rational -emotive behavior therapy can be done to reduce depression and anxiety in women with chronic disease cases while maintaining the effectiveness the goal of REBT.